Penggunaan Aplikasi WoW (Words of Wonders) dalam Meningkatkan Vocabulary Mastery Siswa di SMP Swasta Amalyatul Huda - Anggraini, Risa; Handayani, Nursyah; Annisa, Julia (LPPM Universitas Potensi Utama, 2022)
Vocabulary is the foundation of language. Students must master vocabulary if they want to become skilled in the language. By mastering vocabulary, students can also master other skills such as speaking skills, writing skills, listening skills, and reading skills. To make it happen, teachers must have the right teaching media. Integrating technology into the teaching and learning of English is certainly one of the effective ways that all English teachers should apply in their class. By understanding and following technological advances, not only teachers, students will also receive a very good impact from this, namely students are able to master and enrich their English vocabulary. Utilization of this technology can be done by applying teaching media such as WoW (Word of Wonders; Crossword) applications or crossword puzzles. This application, of course, is very practical for students to download and get anytime and anywhere. The use of this application is also very easy for students to understand. This of course has a positive impact on improving the quality and ability of students, especially in their English skills. Keywords : English Teaching and Learning, Vocabulary Mastery, WoW Application (Words of Wonders)